Development of Malaysian indigenous microbial online database system - Merican, A.F.; Fung, L.M.S.; Fong, Y.C.; Cheah, K.P.; Yin, K.C.; Ismail, N.; Kaur, S.; Othman, R.Y. (Malaysian Society for Molecular Biology and Biotechnology, 2002)
This paper describes the development of the Malaysian Indigenous Microbial Online Database System (MIMODS). MIMODS contains five modules which are the Malaysian Indigenous Algae (MIA), Malaysian Indigenous Bacteria (MIB), Malaysian Indigenous Fungi (MIF), Malaysian Indigenous Protozoa (MIP) and Malaysian Indigenous Virus (MIV). Here we discuss the database design, system design, system development and the interface design.